Factors associated with obesity and weight reduction among people with obesity: A systematic review (2020)
Introduction: Obesity is a non-communicable disease of huge public health importance with several multi-systemic complications. Weight reduction techniques are useful in the management of obesity. The aim of this review was to determine the risk factors, health risks of obesity as well as factors influencing weight reduction among individuals with obesity. Methods: Google, Google Scholar, and Pub Med databases were used to identify studies on obesity that assessed risk factors and complications of obesity plus factors influencing weight reduction among people with obesity. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were used and 914 literature records were retrieved. These were limited to papers published in English up to 2019. We excluded 702 articles that did not match our theme and also excluded an additional 156 full articles due to incompleteness. The evidence available was critically appraised in line with our objectives. Results: Fifty-six articles were reviewed, and it was found that obesity increased with age and was more in women. Inadequate diet, physical inactivity, and metabolic disor¬ders were contributory factors, whereas the main factors associated with greater weight reduction were lower pre-treatment weight, lower waist circumference, doctors as role models, and absence of psychiatric co-morbidities. Conclusions: Proven weight reduction methods are vital for the cost-effective manage¬ment of patients as part of lifestyle modification.